Tell your truth an advocacy campaign for male Filipino victims of child sexual abuse, to empower them, inspire them to disclose their experiences, and seek recovery through professional help - Publico, Andrei Stephen H.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Child sexual abuse is a persistent social issue that affects the lives of children all over the world, and has the potential to cause irrevocable psychological damage to victims for the rest of their lives. The Philippines in particular has become infamous for being a hotspot for the production of child pornography, and recent studies conducted throughout the country have revealed that male children are being abused at rates higher than the female children.

The first National Baseline Study of Violence Against Children in the Philippines has confirmed that male children are being abused at far higher rates than female children, However, male children are much less likely to disclose their experiences compared to female children. This is due to preconceived notions that, as males, they ought to "remain strong" and prevent themselves from showing any kind of vulnerability, and that they are also considered "more resilient" than females. Unfortunately, this has resulted in many social workers and researchers frequently putting more focus on fighting for the rights of the latter. Multiple campaigns have been produced for the sake of providing awareness of the dangers of child abuse, vouching for changes in the system, reasserting to children their rights, or signifying the need for parents to protect their children. However, the majority of these campaigns either focus on protecting children in general, or frame female children as those primarily in need of protection.

Tell Your Truth is an advocacy campaign meant to address male victims of child sexual abuse who have not disclosed their experiences to anyone, as well as non-victims who are completely unaware of the plight male victims face. By exploring the concept of narratives as a method of eliciting empathy from the masses, the ultimate goal of the campaign is to inspire male victims of sexual abuse to talk about their experiences and seek professional help to recover from their trauma. All the while, other survivors may be compelled to discuss their own experiences; non-victims would be fully aware of the plight these men face, and would be compelled to fight for their rights as well.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 216-220
Keywords: Male sexual abuse victims -- Rehabilitation -- Philippines; Child sexual abuse -- Philippines; Activism -- Philippines